Analisis Kebutuhan Pelatihan - Azzah Kamila; Sabila Sofiannisa; Adinda Zahro Melati; Machdum Bachtiar (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Human resource development is a strategic factor in improving organizational competitiveness and effectiveness. In a dynamic business environment, organizations are required to develop competent employees through well-planned training programs. This paper aims to analyze the importance of Training Needs Analysis (TNA) in designing effective training programs and to explain the stages of training implementation and evaluation in human resource development. The method used is a literature review with a descriptive-analytical approach, based on relevant concepts, theories, and previous studies related to training, human resource development, task and competency analysis, individual analysis, and training evaluation. The findings show that TNA plays a crucial role in identifying competency gaps at the organizational, task, and individual levels, so that training programs can be more targeted, efficient, and relevant. In addition, training effectiveness is influenced by the selection of appropriate methods, such as on-the-job training and off-the-job training, as well as managerial support and participant readiness. Evaluation is also essential to measure the impact of training on employees’ knowledge, skills, attitudes, and work performance. Therefore, TNA is not only a tool for identifying training needs, but also a strategic foundation for developing competent, productive, and competitive human resources that can support the achievement of organizational goals in a sustainable way. Through systematic planning, proper implementation, and continuous evaluation, training programs can contribute significantly to long-term organizational success and employee performance improvement.